The Enigma of Hepatitis E Virus - Murrison, Liza Bronner (Gastroenterol Hepatol (N Y), 2017)
Globally, hepatitis E virus (HEV) is the most common cause of acute viral hepatitis. HEV is endemic in many developing countries, yet it is far more common in industrialized, nonendemic countries than previously recognized. Nonetheless, HEV remains poorly characterized and is frequently unidentified or misdiagnosed by clinicians. Manifestation of disease, source of infection, and route of transmission vary by HEV genotype and epidemiology in endemic and nonendemic settings worldwide. HEV infection can be acute or chronic, further complicating the presentation, diagnosis, prognosis, and natural history of disease. However, accurate identification and diagnosis of HEV has important implications for patient management, disease control, prevention efforts, and characterization of mechanisms of transmission and epidemiology. Acute HEV infection is rarely diagnosed in industrialized, nonendemic countries; however, recent seroprevalence data collected using modern, highly sensitive testing assays demonstrate a surprisingly high prevalence of anti-HEV antibodies in these settings, suggesting common subclinical or unrecognized infection. These data suggest widespread underestimation of the global burden, population seroprevalence, and importance of HEV infection. Enhanced capacity for disease recognition, accurate diagnosis, and clinical awareness are critical to improving the management and reducing the burden of HEV infection worldwide.